“I NEVER USE HEADSETS”: WOMEN, WARINESS, AND HYPERVIGILANCE FOR THE INEVITABILITY OF ONLINE HARASSMENT IN GAMING CULTURE - Butt, Mahli-Ann (AoIR Selected Papers of Internet Research, 2019)
The gaming community has been contoured by divisive issues around the exacerbation of sexism, racism, and harassment. These tensions culminated in 2014 in the shape of #gamergate: a decentralised online harassment campaign against women and feminism in gaming. Gamergate continues to intensify a heightened climate of hostility especially felt by women and minorities.This ongoing feminist ethnography has emerged from an imperative to create interventions into the increasing normalisation of online and offline harassment. In it, this research analyses the affective labour of how people navigate and ‘cope’ with discrimination in gaming cultures. This paper will present vignettes of the larger research project of how online harassment has coloured people’s lived experiences, through thick-descriptions of in-depth semi-structured interviews conducted with 7 women who play videogames with their romantic partners. These interviews gesture towards a rich complexity of affective relationships at the nexus of gaming, romantic relationships, and the everyday lived experiences of women. To avoid bringing attention to their gender, harassment, and unwanted confrontations, women are hypervigilant. In similar ways to self-defence tactics, women constantly avoid using headsets to communicate with other players, keep clear of conversations about playing videogames, and minimise the performance of their femininity in public gaming spaces.This paper critically examines the dynamics of how the increasing normalisation and public gamification of online harassment impacts women’s engagement with gaming, as well as how ‘online’ harassment may invade into their intimate relationships and domestic ‘private’ spheres.